1979
DOI: 10.1002/anie.197901701
|View full text |Cite
|
Sign up to set email alerts
|

Flash Vacuum Thermolysis of Doubly Unsaturated Acyl Halides to Give Phenols

Abstract: The simplest dienylketene‐phenol rearrangement has been achieved by vacuum flash thermolysis of sorboyl chloride at 6 × 10−5 torr/660°C. Other dienylketenes can also be generated under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Slopianka et al reported a flash vacuum thermolysis of doubly unsaturated acyl halides to de novo preparation of phenols (Scheme c). The severe reaction conditions (660 °C, 6 × 10 –5 Torr) have largely restricted its synthetic application . Rao and co-workers have modified Slopianka’s procedure by in situ formation of ketenes under relatively mild conditions (Scheme d), and recently, these protocols have garnered much success in Sarpong’s elegant total synthesis of (−)-crotogoudin (Scheme e).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Slopianka et al reported a flash vacuum thermolysis of doubly unsaturated acyl halides to de novo preparation of phenols (Scheme c). The severe reaction conditions (660 °C, 6 × 10 –5 Torr) have largely restricted its synthetic application . Rao and co-workers have modified Slopianka’s procedure by in situ formation of ketenes under relatively mild conditions (Scheme d), and recently, these protocols have garnered much success in Sarpong’s elegant total synthesis of (−)-crotogoudin (Scheme e).…”
mentioning
confidence: 99%
“…The severe reaction conditions (660 °C, 6 × 10 −5 Torr) have largely restricted its synthetic application. 6 Rao and co-workers have modified Slopianka's procedure by in situ formation of ketenes under relatively mild conditions 7 (Scheme 1d), and recently, these protocols have garnered much success in Sarpong's elegant total synthesis of (−)-crotogoudin 8 (Scheme 1e). Despite these achievements, it is notable that there are no examples for phenols with electron-withdrawing groups in Rao's report, and the practical application conditions (180 °C, 5 d, propionic anhydride as solvent in Sarpong's report) are still hard to implement for the majority of the functional groups.…”
mentioning
confidence: 99%